Entrepreneurship of disabled people. An approach to social and labour context (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2019)
This paper entitled “Entrepreneurship of disabled people. Socio-labour contextualization” is part of the Disability and entrepreneurship project. Competencial analysis (CSO2016-75818-R), funded by the MINECO, whose main goal is to analyze the role played by competences —understood as a set of knowledge, skills and abilities— in people with physical and / or sensory disabilities, in the design, development and performance in the field of entrepreneurship. In the initial phase, several specific goals were determined: firstly, showing some distinctive features about the social and labor situation of people with disabilities; secondly, analyzing the role of the active labour policies to overcome the barriers to entrepreneurship of disabled people.The hypothesis of the research considers that people with disabilities are in an unfavourable position to get a job and develop an entrepreneurial activity.Methodologically, the research has twofold approach: quantitative and qualitative techniques. However, in the initial phase is limited to a documentary review and statistical analysis with secondary sources on the subject for the period 2008-2016 in Spain: The Employment of Disabled People, The Annual Report of the Labour Market of Disabled People and Living Conditions Survey.The analysis of the results determines that disabled people have significant difficulties to access to the labour market and entrepreneurship activity. Therefore, it is compulsory to make disabled people visible and to make the people aware of this collective by means of actions that highlight their contributions and foster their socio-labour inclusion.
Keywords: entrepreneurship; disability; labour market; labour policies